Mechanomics pCGIT-hCAV1 - plasmid map - Marta Urbanska (8065124) (2024)
Entry is a part of Mechanomics collection (10.6084/m9.figshare.c.5399826) that contains materials supporting findings presented in the following manuscript: Urbanska, M., Ge, Y. et al., De novo identification of universal cell mechanics gene signatures BiorXiv: https://doi.org/10.1101/2021.04.26.441418; first published: 27th April 2021, last updated: 4th Nov 2024 eLife: https://doi.org/10.7554/eLife.87930; first published: 23rd March 2023, last updated: 27th Dec 2024 The files contain plasmid map of both the plasmid used for CAV1 over-expression (pCGIT-hCAV1) as well as the backbone used for creating it (pCGIT). pCGIT-hCAV1 contains human caveolin 1 under the CAG promoter and dTomato fluorescent marker under internal ribosomal entry site (IRES) downstream of the gene of interest. The cDNA of CAV1 was amplified by PCR, introducing NheI and XhoI restriction sites in the flanking regions. The PCR product was then cloned into the pCGIT destination vector (a kind gift from P. Serup, University of Copenhagen, Denmark).